Penerapan Lean Manufacturing di CV. Wahana Karya - Arie Saputra; Fitriadi Fitriadi; Iing Pamungkas; Khairul Hadi; Muzakir Muzakir (Jurnal Pengabdian Agro and Marine Industry, 2021)
CV. Wahana Karya is one of the companies engaged in the manufacture of ships under 30 GT.  Several ship production activities in CV. Wahana Karya still relies on technical concepts related to production management which are still empirical.In addition, production management which is still traditional in nature often ignores the concept of production management which is more integrated with the principle of improvement at all stages of the production process.  This research was conducted based on previous studies that used the concept of Lean Manufacturing as the basis for empirical calculations through stochastic analytic studies. The parameters carried out in the service are based on relevant research. The results obtained were some waste that was successfully repaired through inventory efficiency of 20.4%, overproduction of 12% and defective products of 15.7%. On the other hand, this service is also able to reduce the completion time of shipbuilding by 9.8%. There is still a deviation in general of an average of 25% from the results of analytical calculations with implementation results. This is due to the need for other supporting studies so that the concept of integration of the intended improvements can be further optimized.